Peripherally Administered Human Umbilical Cord Blood Cells Reduce Parenchymal and Vascular β-Amyloid Deposits in Alzheimer Mice - Nikolic, William V. (Mary Ann Liebert, Inc., 2008)
Modulation of immune/inflammatory responses by diverse strategies including amyloid-β (Aβ) immunization, nonsteroidal anti-inflammatory drugs, and manipulation of microglial activation states has been shown to reduce Alzheimer's disease (AD)-like pathology and cognitive deficits in AD transgenic mouse models. Human umbilical cord blood cells (HUCBCs) have unique immunomodulatory potential. We wished to test whether these cells might alter AD-like pathology after infusion into the PSAPP mouse model of AD. Here, we report a marked reduction in Aβ levels/β-amyloid plaques and associated astrocytosis following multiple low-dose infusions of HUCBCs. HUCBC infusions also reduced cerebral vascular Aβ deposits in the Tg2576 AD mouse model. Interestingly, these effects were associated with suppression of the CD40–CD40L interaction, as evidenced by decreased circulating and brain soluble CD40L (sCD40L), elevated systemic immunoglobulin M (IgM) levels, attenuated CD40L-induced inflammatory responses, and reduced surface expression of CD40 on microglia. Importantly, deficiency in CD40 abolishes the effect of HUCBCs on elevated plasma Aβ levels. Moreover, microglia isolated from HUCBC-infused PSAPP mice demonstrated increased phagocytosis of Aβ. Furthermore, sera from HUCBC-infused PSAPP mice significantly increased microglial phagocytosis of the Aβ(1-42) peptide while inhibiting interferon-γ-induced microglial CD40 expression. Increased microglial phagocytic activity in this scenario was inhibited by addition of recombinant CD40L protein. These data suggest that HUCBC infusion mitigates AD-like pathology by disrupting CD40L activity.